Informational-technological support of professional training of teachers in the system of postgraduate education - Kashina, Ganna (ScienceRise: Pedagogical Education, 2017)
The problems of informational-technological support of professional training of teachers in the system of postgraduate education are considered in the article. The use of informational technologies in all fields of the life determines the essence of changes in educational system. That is why the notion of open education during the life, innovative character of education in informational society and its virtualization are urgent. The stable dependence between the effective activity of a teacher and the level of its professional competence, that is mainly determined not by the volume of mastered content of knowledge but by the development of thinking, ability to self-control of activity, ability to self-education during the life, continuous self-improvement, is observed now. So the determinative precondition of effective professional training of teachers of secondary schools in the system of postgraduate education under conditions of informational society development is a process of improvement of professional qualities and development of teacher’s skills during the whole life, because basic knowledge and skills become insufficient for realization of working tasks with time. Just introduction of informational-technological support of teacher’s professional training in the system of postgraduate education is an effective instrument that realizes the educational principles during the life and favors professional development of teachers, is able to provide communication between all subjects of educational system, continuous consulting, informing and renewal of learning materials at all stages of the study. Organization of the study of teachers in the system of postgraduate education using informational-technological support must take into account the features of adult training. Because just the use of informational-technological support for professional training of teachers and their comprehension of informational-communicational technologies as an instrument and environment of professional development, readiness to the study with informational-communicational technologies is an indicator of ability to professional development and self-development, level of informational-communicational competence formation, main directions of their improvement. The use of informational-technological support of teachers’ professional training in the system of postgraduate education opens the considerable possibilities as to creation of continuous education of a teacher according to the modern educational requirements